Uterine smooth muscle tumor of uncertain malignant potential: a three-case report. Issue 5 (1st August 2008) - Berretta, R.; Rolla, M.; Merisio, C.; Giordano, G.; Nardelli, G. B.
Abstract : Based on the degree of cytologic atypia, mitotic activity, and other features, uterine smooth muscle tumors have historically been grouped into two classes: benign leiomyomas and malignant leiomyosarcomas. However, this separation holds true more in principle than in practice because the tumor's biological potential may not always be determined with certainty, complicating diagnosis, and therapy. We report three cases of patients with uterine smooth muscle tumors of uncertain malignant potential. Surgery was radical in two and conservative in one. During the follow-up, one patient developed diffuse lung metastases. The two other patients have not shown any signs of relapse to date. Uterine smooth muscle tumors of uncertain malignant potential may have an unpredictable clinical course and may metastasize to seemingly low-grade neoplasms in distant sites even after several years and even in the absence of important negative prognostic predictors, such as coagulative tumor cell necrosis. At present, no final consensus has been reached on the choice of the best strategy for surgery and adjuvant therapy